Measuring Everyday Life Talking About Research and Why It Matters - Southwell, Brian G.; Jackson, Karen Keaton; Pittman-Blackwell, Bridget (RTI Press Publication, 2022)
Why do people act as they do? How can we improve our health and well-being? What can the past tell us about our future? Research can help us address such questions, but the journey to finding answers can be challenging and full of adventure. Curated from interviews featured on the public radio show, The Measure of Everyday Life, this collection reveals ways that we can ask useful questions. The book also offers insights from behind the scenes of social science research, communication campaigns and interventions, and community engagement projects. A wide range of audiences-including anyone interested in applying academic research to practical projects, new graduate students, and undergraduate students learning about research-should find useful material in the collection.